2021
DOI: 10.1055/s-0041-1731764
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Vertical Profunda Artery Perforator Flap to Capture the Dominant Perforator: A Cadaver Dissection and Imaging Study

Abstract: Introduction While the originally described transverse profunda artery perforator (tPAP) flap is designed to capture the first profunda perforator, our group hypothesized the dominant perforator may not always be captured in this configuration. This study maps the location of dominant profunda perforators using imaging and cadaveric dissections to determine the probability of capturing dominant perforators with the transverse flap design versus the vertical PAP (vPAP) variant. Methods Fifty preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Our study evaluated the PAP anatomy through a cadaveric study to determine the detailed anatomic information of the perforators from the profunda femoris artery. The average distance from the origin of perforators to the gluteal sulcus was 71.72 mm, which is similar to the reported average perforator distance by Jourdain et al of 71.6 mm below the gluteal sulcus (20). However, another anatomic study by Allen et al has reported a shorter average distance inferior to the gluteal crease of 3.5 cm (13).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our study evaluated the PAP anatomy through a cadaveric study to determine the detailed anatomic information of the perforators from the profunda femoris artery. The average distance from the origin of perforators to the gluteal sulcus was 71.72 mm, which is similar to the reported average perforator distance by Jourdain et al of 71.6 mm below the gluteal sulcus (20). However, another anatomic study by Allen et al has reported a shorter average distance inferior to the gluteal crease of 3.5 cm (13).…”
Section: Discussionsupporting
confidence: 84%
“…The PAP flap has become a popular secondary option for autologous breast reconstruction because of its advantages including a hidden scar, and this technique is useful in slim patients who do not have sufficient abdominal volume (15). Previous studies have reported an anatomic analysis of the PAP flap (12,13,(16)(17)(18)(19); however, a detailed anatomic study has not been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study advocated that the vertical PAP flap with multiple perforators has advantages over the transverse PAP flap, 24 25 including multiple perforators and flexibility in utilizing distal and larger perforators. However, a vertical visible scar could not be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, based on proximal musculocutaneous perforators from the adductor magnus (AM) muscle, it was initially referred as “adductor flap” by Angrigiani et al ( 2001 ). Later, further publications have then better elucidated PAP's anatomy and identified clinical applications (Ahmadzadeh et al, 2007 ; Allen et al, 2012 , 2016 ; Artz et al, 2021 ; Haddock et al, 2012 ; Hammond et al, 2021 ; Saad et al, 2012 ; Scaglioni et al, 2015 ; Song et al, 2020 ; Wong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%